Management practices for engaging a diverse workforce : tools to enhance workplace culture - Gupta, Manish, 1987-; Gupta, Manish (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"This unique volume, Management Practices for Engaging a Diverse Workforce: Tools to Enhance Workplace Culture, shows how to tackle the challenges of diversity in the workplace. It addresses the need to keep the workforce engaged while taking into consideration the diverse backgrounds of employees. The book explores 12 themes of workforce diversity and culture, including differences of race, religion, gender, sexuality, income class, education level, marital status, generation/age, physical ability, and more. Focusing on the benefits of engaging a diverse workforce, the volume considers the issue through the different stages of the human resource process, including recruitment, selection, performance appraisal, demand forecasting, supply forecasting, job description and specification, job analysis and evaluation, training and development, career planning and development, succession planning, etc. Employing an abundance of case studies, the volume enables readers to comprehend what it means to have a diverse workforce and how to engage such a workforce for the betterment of the employees as well as the employer. The volume acts as a textbook for courses on diversity in human resource management as well as a valuable resource for HRM and other management professionals. The discussions and questions sections will be useful for faculty, and the short case studies are designed to keep students interested-and engaged. The chapter authors follow a standard structure throughout the book, introducing the particular theme of workforce diversity followed by the significance of the theme, a review of the theme, the implications of the theme, and a conclusion. Key features: Discusses many diverse types of employees, including race, gender, sexuality, education level, age, and more Includes an abundance of short case studies based on real and hypothetical incidents Provides brief descriptions of a particular type of workforce diversity Includes case discussions to help teachers direct a case toward concept and make the student know the possible case solution Includes critical questions to brainstorm each concept"--
OCLC-licensed vendor bibliographic record.
Keywords: Diversity in the workplace; Personnel management; Corporate culture; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Workplace Culture